The resilience landscape - Bhandary, Prapti; Ringler, Claudia; De Pinto, Alessandro (International Food Policy Research Institute, 2019)
This study, while focusing on climate resilience adopts the broader definition of resilience from the United Nations International Strategy for Disaster Reduction which defines resilience as: “the ability of a system, community or society exposed to hazards to resist, absorb, accommodate, adapt to, transform and recover from the effects of a hazard in a timely and efficient manner, including through the preservation and restoration of its essential basic structures and functions through risk management” (UNISDR 2017). Resilience thinking helps link and integrate sectors such as infrastructure, social protection, health and reproductive health, and nutrition that have traditionally been somewhat disconnected. To ensure that appropriate connections are made, this report proposes that the government of Ethiopia and partners develop or use a resilience framework, according to which its many development programs can be structured and monitored for progress and outcomes.